Механізм формування цін і тарифи у динамічній моделі невеликої відкритої перехідної економіки - Oganesyan, Gayane (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2010)
This paper examines the importance and dynamics of prices in a small open economy in transition. Several main features of this process outline the behavior of the mathematical model. The model examines four factors that affect prices after the liberalization of the domestic market: the domestic producer price, the cost price of inefficiency, the hyperinflation price, and the world market price, which includes the dynamics of the exchange rate. The numeric simulation of the price dynamics for the cheese segment of Ukrainian food market was made.